A implementação da Lei nº 10.639/03 em cursos de formação de professores: o discurso institucional da UFMG - Audrey Michele Nogueira (2017)
This master's research aimed to analyze the institutional discourse of the Federal University of Minas Gerais before the demand for implementation of the study/teaching of the History and Culture of Africa and Afro-Brazilian, in the teacher training courses, according to Federal Law No. 10,639 / 2003. Such legislation is part of the struggle against racial inequality in Brazil and is effective as a normative that questions the curriculum as an element of domination and power. We are anchored in the Critical Discourse Analysis as a theoretical-methodological aspect, as it emphasizes the social dimension of language. The discourse is an integral element of society, and as social practice, it emerges amidst the relations of conflict and power, being at the same time an instrument of domination and an instrument of change. We realized that racism strengthened by the discourse of the myth of racial democracy and by the lack of critical knowledge of the subjects about ethnic-racial relations in Brazil is the great impediment to the process of implementing Law 10,639 / 03. The subjects endowed with the power of a position, are those that will make viable or not the processes of implementation of a Legal demand. And within the ambit of said Law, we have seen that there is a strong need to raise awareness and even convince the academic community about such demand. On the other hand, the process of implementation of the Law gains strength, due to the antiracism evidenced through the actions of counter-power, and made possible by the active access of black minorities, militant students and teachers and dissidents of the white group, who struggle to claim and develop numerous promotion strategies of racial equality, which are gradually being incorporated by the institution. With the internal pressures of militancy and the external pressure of the MEC evaluations, the University starts to present a discourse of institutional response, are still timid actions built in the middle of a lot of resistance, but which reveal a movement more favorable to the incorporation of re-education into ethnic relations by the institution